RANCANG BANGUN APLIKASI AKREDITASI TEKNIK INFORMATIKA PADA STUDI KASUS STANDAR 7 - Sugiarti Sugiarti; Saiful Bahri; Donna Setiawati (Universitas Boyolali, 2018)
Sugiarti,C14020003. The research of the Design Building for Accreditation of Information technology has been done in Boyolali University at May 30th untill August 15th 2017. The research taken because in Boyolali University the acreditation file still done manually. Boyolali University need aplication that can makes the acreditation files easier. The result application is web application and can help Boyolali University to make acreditation file easier. The design of application use FAST methode. Fast methode steps are analysis, system development, logical design, physical design and implementations. This methode help to develop the system to provides a mechanism for understanding and analysis user needs, doing negotiation, selection of variable solutions. The creation of an organize system and system implementation. So this application can increase work efficiency.